STYLISTIC FEATURES OF THE RUSSIAN LANGUAGE AND THEIR USE IN LITERATURE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the place of the Russian language in the science of stylistics, its main stylistic layers, the use of language tools in fiction, and the aesthetic value of the artistic images created through them. The history of the Russian literary language, its stylistic richness, and the individual style of writers are also studied stylistically, highlighting the artistic impact of these features on literature. Along with theoretical information, the article also provides a practical approach to stylistic issues through the analysis of classical literary samples.